Successful pilot implementation of mailing lethal means safety devices to veterans calling the Veterans Crisis Line - Landes, Sara J.; Bourgeois, Jolie E.; Curtis, Nyssa D.; Thropp, Jennifer E.; Panal, Ethan R.; Spitzer, Elizabeth G.; Jegley, Susan M.; Lauver, MaryGrace (Frontiers in Psychiatry, 2024)
Veterans are at greater risk for suicide than non-veterans; veterans who call the Veterans Crisis Line are at even higher risk. Firearms and poisoning are among the most common methods by which people die by suicide in the United States and access to those lethal means are risk factors for suicide. The United States Department of Veterans Affairs' Veterans Crisis Line conducted a six-month pilot to enhance lethal means safety counseling conversations by mailing lethal means safety devices (cable gun locks and/or medication takeback envelopes) to veteran callers.Veterans Crisis Line responders were selected based on quality assurance ratings, received training, and passed a knowledge check prior to participating. Veterans were eligible if they were calling for themselves and had access to firearms and/or surplus medications. The pilot was assessed using operational data and qualitative interviews with responders to assess their experience, barriers and facilitators, and suggestions for improvement.Responders documented 8,323 calls from 7,005 unique phone numbers; 10.8% were eligible for cable gun locks and 8.7% were eligible for medication takeback envelopes. Responders offered cable gun locks to 652 veterans and medication takeback envelopes to 522 veterans. A total of 465 cable gun locks and 567 medication takeback envelopes were mailed to 307 veterans.Operationally, there was little impact of the pilot on call handle time. Five responders participated in qualitative interviews. They reported feeling comfortable incorporating mailing devices into their work and reported that response from veterans was positive. Their most frequent suggestion for improvement was additional training.Results demonstrate that mailing these devices to veterans was feasible and acceptable. Call handle time results show that the Veterans Crisis Line would not need additional personnel to manage changes in call handle time associated with offering devices to all veteran callers. Full implementation of this program will require updates to procedures and policies, training, documentation system changes, additional logistical support for mailing, and a plan for ongoing evaluation.